Sovrapposizioni di disuguaglianza e percorsi educativi. Un’esperienza nell’era del Covid - Grignoli, Daniela; Boriati, Danilo (Filosofia Morale/Moral Philosophy, 2023)
The pandemic period has demonstrated and has “discovered” how some kinds of inequality (“educational poverty” among them), which is already marked by many factors that cause these vulnerabilities, are influenced by additional elements that, especially in periods of emergency, emerge with all their unquestionable importance in fostering and promoting further and more serious inequalities, inequities and differences, locally and globally. Within this framework, the essay – through the results of empirical research carried out (in three different areas of Italy) – proposes suggestions for a reflection on educational poverty and on interventions for possible social development.